C‐Src activation as a potential marker of chemical‐induced skin irritation using tissue‐engineered skin equivalents. Issue 2 (11th December 2022) - Harding, Amy L.; Colley, Helen E.; Vazquez, Inmaculada Barragan; Danby, Simon; Hasan, Md Zobaer; Nakanishi, Hirofumi; Furuno, Tetsuo; Murdoch, Craig
Abstract: Skin irritancy to topically applied chemicals is a significant problem that affects millions of people worldwide. New or modified chemical entities must be tested for potential skin irritancy by industry as part of the safety and toxicity profiling process. Many of these tests have now moved to a non‐animal‐based format to reduce experiments on animals. However, these tests for irritancy potential often rely on monolayer cultures of keratinocytes that are not representative of the skin architecture or tissue‐engineered human skin equivalents (HSE) using complex multi‐gene expression panels that are often cumbersome and not amenable for high throughput. Here, we show that human skin equivalents increase abundance of several phosphorylated kinases (c‐Src, c‐Jun, p53, GSK3α/β) in response to irritant chemical stimulation by phosphokinase array analysis. Specific phosphorylation of c‐Src Y419 was confirmed by immunoblotting and was plasma membrane‐associated in basal/spinous cells by phospho‐specific immunohistochemistry. Moreover, c‐Src Y419 phosphorylation in response to the irritants lactic acid and capsaicin was inhibited by the c‐Src inhibitors KB‐SRC and betaine trimethylglycine. These data provide the first evidence for c‐Src specific activation in response to chemical irritants and point to the development of new modes of rapid testing by immunodetection for first‐pass screening of potential irritants. Abstract : This study demonstrates that specific kinases, in particular c‐Src, are activated in HSE in response to chemical irritants. The rapid increase in specific phosphorylated signal transduction molecules upon exposure to irritants may prove ideal targets to rapidly identify and differentiate potential chemical irritants from non‐irritants.